Digital Marketing: Solution for Market Expansion of MSME Products : Digital Marketing: Solusi Perluasan Pasar Produk UMKM - Sumarmi, Saptaningsih; Anindyasari , Vientika Ravintan; Adhiany , Lintang; Lestari , Fransisca Jenny Eka; Fauziana , Atika; Tentua , Meilany Nonsi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The creative economy has emerged as a catalyst for economic advancement in Bantul Regency, and through the proliferation of craft centers, culinary and industrial enterprises, and the tourism sector, all poised to offer investment prospects. Nonetheless, the advancement of this sector is hindered by the limited capacity of business stakeholders to extend their market outreach. Focusing on the culinary domain, the outreach team assists Small and Medium Enterprises (SMEs) by imparting knowledge and guidance concerning the significance of adhering to business regulations and licensing. They are adopting digital marketing approaches to amplify their market presence. After training, practical sessions, and mentoring, entrepreneurs now hold a NIB and P-IRT, empowering them to promote their products under their brand identity. These business operators have enthusiastically embraced digital marketing methodologies to market their wares. They are devising plans for expansion, including creating a dedicated exhibition space to showcase their merchandise